Search for events in XENON1T associated with gravitational waves - Aprile, Elena; Abe, K.; Ahmed Maouloud, S.; Althueser, L.; Andrieu, B.; Angelino, E.; Angevaare, J. R.; Antochi, V. C.; Antón Martin, D.; Arneodo, F.; Baudis, L.; Baxter, A. L.; et al. (Physical review, 2023)
We perform a blind search for particle signals in the XENON1T dark matter detector that occur close in time to gravitational-wave signals in the LIGO and Virgo observatories. No particle signal is observed in the nuclear recoil and electronic recoil channels within ±500 seconds of observations of the gravitational-wave signals GW170104, GW170729, GW170817, GW170818, and GW170823. We use this null result to constrain monoenergetic neutrinos and axion-like particles emitted in the closest coalescence GW170817, a binary neutron star merger. We set new upper limits on the fluence (time-integrated flux) of coincident neutrinos down to 17 keV at the 90% confidence level. Furthermore, we constrain the product of the coincident fluence and cross section of axion-like particles to be less than 10−29 cm2/cm2 in the [5.5-210] keV energy range at the 90% confidence level.
Gesehen am 16.07.2024